Enhancing Email Client Security with HMAC and PGP Integration to Mitigate Cyberattack Risks - Oktaviani, Ayu Nur; Hadiana, Asep Id; Melina, Melina (International Journal of Quantitative Research and Modeling, 2024)
The rapid advancement of technology in the modern era has significantly increased the risk of data breaches and misuse, particularly in email communications. Ensuring data privacy and security is crucial to preventing information theft and mitigating cyberattack risks. This research focuses on enhancing email client security through the integration of Hash-Based Message Authentication Code (HMAC) and Pretty Good Privacy (PGP). HMAC is employed as a message authentication mechanism to ensure the integrity and authenticity of email messages, while PGP is utilized to generate public and private key pairs, enabling secure encryption and decryption processes. By integrating these two security methods into the email client system, we aim to enhance its resilience against cyber threats. The system's effectiveness was evaluated through black-box testing, demonstrating its capability to secure the email delivery process. Additionally, an analysis of key randomness using the entropy method revealed a maximum value of 6 bits, indicating a relatively high level of randomness and further strengthening the encryption process. The results of this study indicate that the combined use of HMAC and PGP provides a robust security solution for enhancing email client security and mitigating potential cyberattack risks.